Very rich - Horvath, Polly (Margaret Ferguson Books, Holiday House, 2018)
Ten-year-old Rupert, from a very large, very poor family, accidentally becomes part of an eccentric rich family's life beginning at Christmas, and soon sees that wealth is not everything.